The representation of 'Others' in East Asian television advertisements. (February 2022) - Prieler, Michael; Ivanov, Alex; Hagiwara, Shigeru
This study conducted a content analysis of 442 television advertisements from Hong Kong, Japan, and South Korea to determine their representations of 'Others'. Findings reveal that in East Asian advertisements, Others are overrepresented, mostly non-celebrities, and depicted in major roles, which is in contrast to previous studies in the United States where 'Others' are generally shown in minor or background roles. The results also reveal that Others are predominantly white, demonstrating the importance of whites in these societies and representing some type of racial/ethnic hierarchy. However, Others are also depicted as separate from the majority population. For example, they are usually depicted abroad rather than in a local setting, and they rarely interact with the local population, which sends a message of exclusion and might lead to the conclusion that they do not belong to their respective location. Possible effects and practice implications of these findings are discussed.